'All the things happening outside of the museum push me back in': thinking through memory and belonging in Amsterdam's Tropenmuseum. Issue 1 (2nd January 2022) - Caradonna, Vittoria
ABSTRACT: Through a close examination of the exhibition Afterlives of Slavery, which opened on 6 October 2017 at the Tropenmuseum in Amsterdam, this article interrogates the issues and contradictions emerging from thinking through decoloniality – from within the halls of an ethnographic museum located at the centre of the former colonial metropole. In recent years, the Tropenmuseum has been engaged in a process of reckoning with its position within the history of empire. To which ends does decolonial thinking enter the institution? And where does the museum situate itself within broader processes of memorialisation and heritagisation of slavery and colonialism? Drawing from extensive fieldwork and interviews with key informants, this article will attempt to answer these questions by exploring the tensions an exhibition such as Afterlives of Slavery has opened inside the museum.